Strategic Leadership Analysis of School Principal to Improve Learning Quality - Safrida Safrida; Hendy Tannady; Everhard Markiano Solissa; Heppy Sapulete; Gamar Al Haddar (STKIP PGRI SITUBONDO, 2023)
To create a good quality of generation, education must be carried out from an early age, in this case through Early Childhood Education (PAUD), namely education aimed at children from birth to the age of six. Quality education is not only seen from the quality of its graduates, but also includes how schools are able to meet customer needs in accordance with applicable quality standards. Principals are required to have the right leadership and strategy to increase the professionalism of teaching staff in their schools, so they are able to create a conducive school climate, provide advice to school members, provide encouragement to all teaching staff and implement an interesting learning model. In addition to carrying out its functions, the principal has the task of developing a strategy and mission so that he knows which way to go and knows how to get there in order to achieve the operational goals of an educational institution. In improving the quality of education the principal must improve the quality of a teacher in order to achieve a better quality of education. Make a program in one academic year, in the form of an annual program and a semester program. Adding infrastructure so that the teaching and learning process can run well.